2018
DOI: 10.1021/acs.jctc.8b00033
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Sampling of Hydrogen Bond Networks for Computational Protein Design

Abstract: Hydrogen bond networks play a critical role in determining the stability and specificity of biomolecular complexes, and the ability to design such networks is important for engineering novel structures, interactions, and enzymes. One key feature of hydrogen bond networks that makes them difficult to rationally engineer is that they are highly cooperative and are not energetically favorable until the hydrogen bonding potential has been satisfied for all buried polar groups in the network. Existing computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Adjacent hydroxyl groups on B ring of avonols might increase its electron cloud density, which was benecial for hydrogen atoms donation to form hydrogen bonds easier with active-center residues of a-glucosidase. It was reported that hydrogen bonds formation could help to increase the stability of complex, 51,52 so the inhibitor bound more tightly to enzyme and enhanced its inhibition activity. Therefore, it was proposed that a-glucosidase inhibitory effects of these avonols were enhanced with increase number of hydroxyl groups at their Bring, which was consistent with the results of in vitro enzyme activity test.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Adjacent hydroxyl groups on B ring of avonols might increase its electron cloud density, which was benecial for hydrogen atoms donation to form hydrogen bonds easier with active-center residues of a-glucosidase. It was reported that hydrogen bonds formation could help to increase the stability of complex, 51,52 so the inhibitor bound more tightly to enzyme and enhanced its inhibition activity. Therefore, it was proposed that a-glucosidase inhibitory effects of these avonols were enhanced with increase number of hydroxyl groups at their Bring, which was consistent with the results of in vitro enzyme activity test.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…In other words, obtaining a sequence with a fully connected network from a sequence with no hydrogen bond network requires that the sequence optimization simulation pass through intermediate sequences with high energies. To address this issue, a side-chain sampling protocol that uses a graphical representation of potential hydrogen bond partners was developed to enumerate all possible side-chain hydrogen bond networks for an input backbone structure [107][108][109] . This method allowed the design of helical oligomers with large numbers of buried polar amino acids and high binding specificities between the protein chains.…”
Section: Optimizing the Protein Sequencementioning
confidence: 99%
“…We then select out the small fraction of the fusions in which the joined DHRs are in contact beyond the superimposed junction helix to reduce flexibility across the junction by requiring that at least two helices from each DHR make contact across the new interface. We also filtered out models with buried unsatisfied hydrogen bonds (13) and then used Rosetta de novo structure prediction calculations to identify sequences strongly specifying the designed structures in silico (Fig. 1D).…”
Section: Significancementioning
confidence: 99%